Reformasi Orientasi Dan Sistem Penilaian Konerja Pegawai Negeri Sipil: Mengapa Dan Bagaimana? - Yeremias T Keban (JKAP (Jurnal Kebijakan dan Administrasi Publik), 2005)
This article discuss two important subjects. First, it argues that Indonesian government should reform their performance appraisal system. Second, the recommendation to improve the performance appraisal system for civil servants. There are three reasons argued by the author of why Indonesian government should reform their performance appraisal system for civil servants: First, the system is not academic enough in term of the instruments which are used; second the method is not effective, lastly the system could not be used to diagnose to provide feed backs to improve the performance of the civil servants. To prevent the inefficiency, the author strongly suggest that the government should take immediate action to replace the old system with the new ones which is recommended from this article.